Replication-deficient herpes simplex virus type 1 virus vaccine - LIU YONGHONG; LIU YUANYUAN; DENG TIANYI; ZENG YUYUN; CHEN XIAOQING; ZHOU GUOYING (2025)
The invention discloses a replication-deficient HSV-1 (herpes simplex virus type 1) virus vaccine. The replication-deficient HSV-1 virus vaccine comprises a modified HSV-1 genome and at least one antigen. The modification includes a deletion of an internal repetitive sequence, an inactive mutation in ICP47, and an inactive mutation in another copy of ICP4. A first antigen of the at least one antigen is driven by a promoter of an immediate early gene, such as ICP4. In particular examples, the HSV-1 viral vaccines express antigens from SARS-Cov, SARS-Cov-2, and variants thereof, and are used to induce an immune response against Sabebe virus in a subject to which the vaccine is administered. 本发明公开了一种复制缺陷型HSV-1病毒疫苗，该复制缺陷型HSV-1病毒疫苗包含经修饰的HSV-1基因组和至少一种抗原。该修饰包括内部重复序列的缺失、ICP47中的失活突变和ICP4的另一拷贝中的失活突变。该至少一种抗原的第一抗原由立即早期基因诸如ICP4的启动子驱动。在具体的示例中，该HSV-1病毒疫苗表达来自SARS-Cov、SARS-Cov-2以及它们的变体的抗原，并用于在施用该疫苗的受试者中诱导针对沙贝病毒的免疫应答。